A Multivariate Analysis of Smartphone Use Behavior Among Motorcyclists at Urban Intersections - Surinaud, Ekarin; Tankasem, Phongphan; Leeanansaksiri, Anuchat (Salehan Institute of Higher Education, 2026)
The increasing use of smartphones while riding motorcycles poses significant safety risks, particularly in urban environments of middle-income countries with high motorcycle usage. Despite growing global concerns, limited research has examined the combined influence of individual, behavioral, and environmental factors on smartphone use among motorcyclists at signalized intersections. This study investigates the determinants of smartphone use behavior—both hand-held and hands-free—among motorcyclists in Khon Kaen City, Thailand. A total of 31,648 riders were observed using video surveillance across eight intersections with varying geometric and land-use characteristics. As part of the methodological approach, binary and multinomial logistic regression models were applied to analyze factors associated with smartphone use. The results show that 7.7% of motorcyclists used smartphones while riding, with 6.2% using hand-held and 1.5% using hands-free modes. Significant predictors included riding alone, being male, not wearing a helmet, riding during nighttime or weekdays, and stopping at red lights. Delivery riders were particularly likely to use smartphones, especially in hands-free mode. These findings highlight the multifaceted nature of distracted riding and suggest the need for comprehensive, context-sensitive policy interventions. The insights gained from this study can inform strategic planning and safety enforcement not only in Thailand but also in other urban areas across middle-income countries where motorcycles remain a dominant mode of transport.